Synthesis of β-Phenethyl Ethers by Base-Catalyzed Alcohol Addition Reactions to Aryl Alkenes - Luo, Chaosheng; Bandar, Jeffrey S. (Synlett, 2018)
The direct anti-Markovnikov addition of alcohols to styrene derivatives represents a streamlined route to β-phenethyl ethers, a substructure frequently found in pharmaceuticals and other bioactive molecules. Here, we discuss how the development of such a reaction can complement and address limitations of current methods for β-phenethyl ether synthesis. In particular, we highlight our recent approach toward achieving this challenging alcohol addition reaction through P4-t-Bu superbase catalysis. A summary of compatible aryl alkenes and alcohols is provided to inform readers of potential applications of this new catalytic transformation, as well as its current limitations and future directions.1 Introduction2 Anti-Markovnikov Alcohol Addition to Aryl Alkenes: Background3 Superbase-Catalyzed Alcohol Addition to Aryl Alkenes4 Summary and Outlook
Keywords: phosphazene superbases; Brønsted base catalysis; anti-Markovnikov addition; ether synthesis; alcohols; aryl alkenes